2009
DOI: 10.1063/1.3093816
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization dynamics and Gilbert damping in ultrathin Co48Fe32B20 films with out-of-plane anisotropy

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 19 publications
5
58
0
1
Order By: Relevance
“…1(a). A coercive field less than 0.01 T (inset) is typical of CoFeB films with PMA [18,16]. Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1(a). A coercive field less than 0.01 T (inset) is typical of CoFeB films with PMA [18,16]. Table 1.…”
mentioning
confidence: 99%
“…1(a). A coercive field less than 0.01 T (inset) is typical of CoFeB films with PMA [18,16]. M S and t MDL can be extracted from the slope and x intercept, respectively, and are summarized in Table 1.…”
mentioning
confidence: 99%
“…Recent studies have shown that the damping of precessional dynamics in ferromagnetic metals can be complicated by the action of many extrinsic damping processes such as inhomogeneous broadening, 15 two-magnon scattering, [16][17][18] interface effects, 19 and spin diffusion into adjacent metallic layers, 14,15,20 with Cr in particular shown to be a strong spin scatterer. 21 Müller et al observed a sharp increase in the damping in CrO 2 films above a threshold pump fluence, possibly due to spin-wave instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…These cannot be achieved simply by engineering the geometrical asymmetries in the nanometer-scale range, but rather require harnessing the induced spinorbit interaction at the interface of the ferromagnetic film to obtain perpendicular magnetic anisotropy (PMA) 2 . Hence an increasing effort is invested in the quest for perpendicular magnetized materials having large anisotropies with low Gilbert damping [3][4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%